Kehidupan Masyarakat Korban Lumpur Lapindo Selama 14 Tahun (2006-2020) di Kecamatan Porong Kabupaten Sidoarjo - Wibowo Kusumo, Bagus (Universitas Islam Negeri Sunan Ampel, 2022)
This research originated from the researcher's interest in the sosial changes that have occurred or experienced by the Lapindo mudflow victims for 14 years, especially the Lapindo mud victims who live in the Porong sub-district, Sidoarjo regency. There have been many changes in the lives of the victims of the Lapindo mudflow during the 14 years after the disaster. Therefore, the problem studied is about how the forms of sosial changes are and what faktors cause sosial changes experienced by the Lapindo mudflow victims for 14 years in Porong sub-district, Sidoarjo regency. This research was conducted in Porong sub-district Sidoarjo regency. The method used in this research is descriptive qualitative by collecting observation data, interviews and documentation. This phenomenon can be attributed using Agil Talcott Parsons's Theory. The findings of the research show that the victims of the Lapindo mudflow for 14 years after the Lapindo mud disaster experienced many changes in their lives. There are those who experience changes in customs, experience changes in their livelihoods or experience changes from the economic aspect, and of course a change in the mindset of the Lapindo mudflow victims.